Thermal expansion of SiC at high pressure‐temperature and implications for thermal convection in the deep interiors of carbide exoplanets. Issue 1 (14th January 2017) - Nisr, C.; Meng, Y.; MacDowell, A. A.; Yan, J.; Prakapenka, V.; Shim, S.‐H.
Abstract: Recent astrophysical observations have shown that some stars have sufficiently high carbon‐to‐oxygen ratios and may host planets composed mainly of carbides instead of silicates and oxides. From the low thermal expansion of SiC at 1 bar, it can be inferred that the buoyancy force of thermal anomalies is much lower in the carbide planets than in the silicate planets. However, numerous studies have shown that high pressure in planetary interiors can fundamentally change the physical properties of materials. We have measured the pressure‐volume‐temperature relations of two SiC polymorphs (3C and 6H) at pressures and temperatures up to 80 GPa and 1900 K and 65 GPa and 1920 K, respectively, in the laser‐heated diamond anvil cell combined with synchrotron X‐ray diffraction. We found no evidence of dissociations of these phases up to our maximum pressure condition, supporting the stability of SiC to 1900 km depth in Earth‐size Si‐rich carbide planets. Following the Mie‐Grüneisen approach, we fit our data to the Birch‐Murnaghan or the Vinet equations of state combined with the Debye approach. We found that the pressure‐induced change in the thermal expansion parameter of SiC is much smaller than that of Mg silicate perovskite (bridgmanite). Our new measurements suggest that the thermal buoyancy force may be stronger in the deep interiors of Si‐rich carbide exoplanets than in the "Earth‐like" silicate planets. Key Points: Silicon carbide would be stable in the mantles of Earth‐size Si‐rich carbide exoplanets The thermal expansion parameter of SiC is greater than that of Mg‐silicate at high pressure Thermal convection may play a more important role at greater depths in Si‐rich carbide planets than silicate planets